2023
DOI: 10.2965/jwet.23-040
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Added Sediment Microbial Fuel Cells to Suppress Phosphorus Release from Sediment in an Agricultural Drainage

Gamamada Liyanage Erandi Priyangika Perera,
Morihiro Maeda,
Hiroaki Somura
et al.

Abstract: Phosphorus (P) release from sediment caused eutrophication in Kojima Lake, Japan. The efficiency of iron-added sediment microbial fuel cells (SMFCs) in regulating P release from agricultural drainage sediment was investigated in this study. Surface sediment collected from an agricultural drainage canal flowing into Kojima Lake was mixed with iron oxide (Fe 2 O 3 ) or amorphous iron oxyhydroxide (FeOOH) at 50 mmol kg −1 . A 14.6-cm high acrylic pipe was filled with 80 mL of deionized water after 130 g of sedime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…Under CC conditions, NH 4 + -N release from sediment was higher than under OC conditions. These results were consistent with Perera et al [39] and Xu et al [54]. In LS-OC treatment, NH 4 + -N reduced significantly at the end due to N immobilization.…”
Section: Amount Of Nh 4 + -N In the Overlying Watersupporting
confidence: 92%
See 3 more Smart Citations
“…Under CC conditions, NH 4 + -N release from sediment was higher than under OC conditions. These results were consistent with Perera et al [39] and Xu et al [54]. In LS-OC treatment, NH 4 + -N reduced significantly at the end due to N immobilization.…”
Section: Amount Of Nh 4 + -N In the Overlying Watersupporting
confidence: 92%
“…Accordingly, we set up the hypothesis that Fe 3+ addition to SMFCs may reduce total phosphorus (TP) release from sediment while producing high electricity. Under short-term SMFC operation for 17 days, we found that high P adsorption by Fe 3+ oxyhydroxides reduced P release from Kojima Lake sediment with high TP content (4.7 g kg −1 ) regardless of SMFC operation until day 15 and then Fe 3+ addition increased P release into the overlying water [39]. Therefore, additional studies on long-term SMFC operations for Fe-added sediment are required.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations